Spinal cord regeneration: the action of neurotrophin-3 in spinal cord injury in rats (Clinics, 2006)
OBJECTIVE: For many years, it was believed that medullary regeneration could not occur, although currently there are many trials using neurotrophic factors, stem cells, fetal medulla grafts, peripheral nerve grafts, and antibodies against myelin-associated proteins that demonstrate the existence of the possibility of spinal cord regeneration. The purpose of this study was to investigate the action of neurotrophin-3, a novel neurotrophic factor. METHODS: The New York University impactor, a standardized device for delivery of spinal cord injuries was used on 33 rats, which were divided into 2 groups: a control group receiving distilled water intraperitoneally and a treatment group receiving neurotrophin-3 intraperitoneally. RESULTS: Using the Basso, Beattie, and Bresnahan scale, the locomotor recovery curve for the neurotrophin-3 treated group was superior to that of the control group (P < 0.05); the administration of neurotrophin-3 was associated with the absence of deaths, while the control group showed a 28.5% (P = 0.026) mortality rate. Other parameters (hematuria rate and histological analysis) showed no significant differences. CONCLUSIONS: Based on these results, it appears that a strong relationship exists between the use of neurotrophin-3 in rats with spinal cord injury and better functional recovery.